2022
DOI: 10.1016/j.jinf.2022.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Routine molecular point-of-care testing for SARS-CoV-2 reduces hospital-acquired COVID-19

Abstract: Objectives Risk of hospital-acquired COVID-19 (HA-COVID-19) infection is increased by cohorting infected and non-infected patients together in assessment areas, whist awaiting laboratory PCR results. Molecular point-of-care tests (mPOCT) reduce time to results and improve patient flow but the impact on HA-COVID-19 is unknown. Methods In this pre and post implementation study patients were evaluated across two time periods: March 1 st to August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…In fact, our results showed that a patient in this group required almost 25 min less than a patient in G1. Routine molecular POCT for SARS-CoV-2 was associated with a reduction in time to results and time spent in admission cohort areas compared to laboratory PCR [18]. An active transition from routine diagnostic laboratories to the realm of high-sensitivity molecular diagnostics can significantly increase the efficiency and responsiveness of POCT and facilitate the management of COVID-19 in multiple settings [19].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our results showed that a patient in this group required almost 25 min less than a patient in G1. Routine molecular POCT for SARS-CoV-2 was associated with a reduction in time to results and time spent in admission cohort areas compared to laboratory PCR [18]. An active transition from routine diagnostic laboratories to the realm of high-sensitivity molecular diagnostics can significantly increase the efficiency and responsiveness of POCT and facilitate the management of COVID-19 in multiple settings [19].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the time of infected individuals in emergency wards could also limit the risks of nosocomial transmission ( 15 , 17 , 18 ). A recent study using another molecular POCT showed that its implementation in the ED was associated with a significant reduction in the rate of hospital-acquired COVID-19 cases ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tazi S et al [ 31 ] showed that the estimated sensitivity and specificity of FilmArray, compared with the MAScIR SARS-CoV-2 M kit 2.0, were 100% and 79.2%, respectively. Recently, Livingstone et al [ 58 ] showed that the application of FilmArray TM RP 2.1 assay for COVID-19 remarkably reduced the time to obtain results spent on assessment cohort wards and the proportion of hospital-acquired COVID-19 infection. The authors concluded that the routine use of molecular point-of-care testing may become the standard of care in hospital admission procedures.…”
Section: Discussionmentioning
confidence: 99%